Pengujian Six Factor Model terhadap Excess Return Saham di Indonesia - Neneng Susanti (Jurnal Pasar Modal dan Bisnis, 2022)
This study aims to determine the effect of the six-factor (market return, firm size, value, profitability, investment, human capital) on excess returns in the manufacturing sector listed on the Indonesian stock exchange for the period 2016 – 2020. The method used in this study is an explanatory method, namely descriptive statistics and verification. The analysis technique in this method uses the eviews 9 application. Based on the research, it can be concluded that partially, market return (X1), firm size (X2), value (X3), and investment (X5) have a significant positive effect on excess return on manufacturing sector companies for the 2015-2019 period. Profitability (X4) and human capital (X6) variables do not have a significant effect on excess return in manufacturing sector companies for the 2015-2019 period.